Analysis of Factors Affecting the Demand of Chicken Egg’s in the Traditional Market of Medan City - Dwi Andini Puspita Sari br Sinaga; Armyn Hakim Daulay; Edhy Mirwandhono; Sayed Umar; Iskandar Sembiring (Jurnal Peternakan Integratif, 2017)
Abstract. The development of the society resulting for animal protein needed such as chicken egg’s increased and affect the demand for eggs in Medan. Therefore, it is necessary to do research to know the factors that influence the demand of chicken egg in traditional market of Medan city at consumer level by using Ordinary Least Square (OLS) method or least squares method with SPSS 22.0 tool. This study was conducted from May to June 2017. This study used primary data obtained from observations and interviews of respondents. The location of the research is determined purposively and the respondent determination by accidental method. Primary data was obtained from 90 consumers of chicken eggs and added with secondary data from government agencies. Then it was analyzed by multiple linear analysis with 5 demand variables namely, the number of dependents, education, income, egg price of chicken, and age. The results showed that all variables simultaneously had a significant effect on demand. Partially only variable of dependent which have real effect to demand of chicken egg of race. So it can be concluded that the demand for eggs in Medan is only influenced by the number of dependents.